EFFICACY OF ENDOSCOPIC TREATMENT FOR PRIMARY VESICO-URETERIC REFLUX IN CHILDREN - Khwaja, Muhammad Athar; Nawaz, Gul; Jamil, Muhammad Imran; Muhammad, Shujah; Rehman, Asad ur; Shohab, Durre; Khan, Iftikhar Ali; Hussain, Ijaz; Iqbal, Waqas; Akhter, Saeed (Journal of Ayub Medical College Abbottabad, 2015)
Background: Vesicoureteral reflux (VUR) is a common anomaly affecting 1-3% of all children and 30-50% of those with urinary tract infection (UTI). In the past febrile vesicoureteric reflux on chronic antibiotic prophylaxis were treated by open surgery. Now a day’s endoscopic injection of a bulking material has replaced open surgical procedure in cases of primary VUR. Our objective was to assess the efficacy of endoscopic treatment for primary vesico-ureteric reflux in children. Methods: This was a descriptive case series. One hundred and five patients with either unilateral or bilateral VUR (181ureters) underwent endoscopic treatment for primary VUR between January 2011 and January 2014. Children from 1 to 12 years of age with grade-II to IV reflux on preoperative voiding cystourethrogram (VCUG) were enrolled through consecutive non-probability sampling. Efficacy of treatment was evaluated at three months post injection by a standard VCUG. Ureters with no or grade-I reflux were considered successful treatment. Results: Out of 105 patients 76 had bilateral while 29 had unilateral reflux. Mean age was 5.7 years (SD±.7). Among 181 refluxing ureters, 116 (64%) were free of reflux, while 49 (27%) showed down gradation and 16 (8.8%) showed no response to treatment on postoperative VCUG. Conclusion: Endoscopic treatment for VUR is a viable option for patients with primary VUR and may be considered in management of such cases.